(untitled) (Colloquia Comparativa Litterarum, 2025)
This article examines two dramatic variations on Denis Diderot’s novel Jacques the Fatalist and his Master from the point of view of the forms of the writer’s empathy. After an overview of contemporary research on the types and definitions of the concept of empathy and a synthesis of Suzanne Keen’s theory of narrative empathy, the plays of Milan Kundera and Éric-Emmanuel Schmitt are studied under the prism of the forms, mechanisms and textual representations of empathy. The concepts of variator, metatextual empathy and intertextual empathy are formulated to define the postures of Kundera and Schmitt in homage to their writing model.